O impacto da cultura pop coreana no Ocidente: a juventude brasileira surfando na Onda Hallyu - Pacheco, Mariana Seminati (2024)
This thesis’s objective is to analyze the South Korean pop movement called Hallyu, which can be translated as Korean Wave, and the transformation into a real hypercultural tsunami, from Asia toward the West, reaching Brazil, and changing the perception about South Korean identity through various media experiences – films, clips, concerts, series, musical bands, fashion and cosmetics, in addition to encouraging language learning and tourism to South Korea. The communicative strategy of this industry, which has massively produced this material, is concerned with occupying social networks and digital platforms, in addition to a notable investment by the government and the business market that feeds a symbolic-economic game, flirting with orientalist stereotypes (Said, 2007), ornamentalisms (Cheng 2018), media flows (Lee, 2018) and body images constituted in different environments (Greiner, 2005). Based on the analysis of some examples of series and musical productions, we seek to collaborate with the state of the art of the discussions, observing the constitution of new subjectivities and the undoing of stereotypes created from the authoritarian narratives of the West, such as the notions of yellow face and yellow peril. The main hypothesis is that, through a strategy of humor, seduction and entertainment, Korean media production has been creating, in its own way, supported by soft-power, anti-colonial fabrications that help rethink stagnant notions of identity in South Korea